HbA1C Variability Is Strongly Associated with Development of Macroalbuminuria in Normal or Microalbuminuria in Patients with Type 2 Diabetes Mellitus: A Six-Year Follow-Up Study. (25th January 2020) - Chiu, Wen-Chan; Lai, Yun-Ru; Cheng, Ben-Chung; Huang, Chih-Cheng; Chen, Jung-Fu; Lu, Cheng-Hsien
Abstract : Background . Glycemic variability is associated with higher risk of microvascular complications in patients with type 2 diabetes. Aim . To test the hypothesis that glycemic variability can contribute to progression to macroalbuminuria in normal or microalbuminuria in patients with type 2 diabetes. Design . This prospective study enrolled 193 patients with type 2 diabetes at a tertiary medical center. Methods . For each patient, the intrapersonal glycemic variability (mean, SD, and coefficient of variation of HbA1c) was calculated using all measurements obtained three years before the study. Patients were divided into four groups stratified by both urine albumin/creatinine ratio and HbA1c-SD. The presence of macroalbuminuria was assessed with Kaplan–Meier plots and compared by log-rank test. Results . Of the 193 patients, 83 patients were in the macroalbuminuria state. Patients in the initial macroalbuminuria group after enrollment had the highest diabetes duration, mean, CV-HbA1c and HbA1c-SD, and uric acid level, and the lowest estimate glomerular filtration rate, followed by subsequent macroalbuminuria and without macroalbuminuria groups. Patients with microalbuminuria and high HbA1c-SD showed the highest progression rate to macroalbuminuria, after a six-year follow-up study by Kaplan–Meier Plots and compared by log-rank test. Conclusions . Higher HbA1C variability is more likely to progress to macroalbuminuria in those patients who are already in a microalbuminuria state. We recommend that clinicians should aggressively control blood glucose to an acceptable range and avoid blood glucose fluctuations by individualized treatment to prevent renal status progression.